Evaluasi Peningkatan Kinerja Guru Dalam Mutu Pendidikan di SD Negeri 230 Palembang - Afriantoni, Afriantoni; Bayhaqi, Muhammad Reyvalza; Maryati, Leni; Tunikmah, Alfia (PGSD Universitas Muria Kudus, 2025)
This study aims to evaluate the improvement of teacher performance in enhancing the quality of education at SD Negeri 230 Palembang. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The research subjects included the principal, teachers, supporting staff, as well as students and parents as additional informants. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that teachers' performance improvement still faces several challenges, such as a lack of effective supervision and limited innovation in teaching strategies. However, the principal's supervision plays a crucial role in supporting teacher performance through continuous guidance and evaluation. The study concludes that enhancing teacher performance can be achieved by optimizing the role of school leadership, providing professional training, and implementing adaptive and innovative teaching strategies, thereby contributing positively to the quality of education at SD Negeri 230 Palembang.